Yield Performance Evaluation of Arabica Coffee Progenies Resulted from Three Way Cross Method - Miftahur Rizqi Akbar; Ari Wibowo; Ucu Sumirat; Dwi Nugroho; Muhammad Fuad Anshori (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2022)
Breeding for high yielding, pest and disease resistance, and good quality Arabica coffee is the direction of the coffee breeding program in Indonesia. Threeway cross-breeding method becomes the alternative method to improve plant genetics to achieve those goals. This research was aimed to evaluate the agronomic performance and grouping of Arabica coffee genotypes from three-way cross progeny. This study was conducted in Andungsari Experimental Station, Bondowoso, East Java from July until September 2021. A randomized complete block design with three replications was used as an experimental design. It consisted of eight Arabica genotypes resulting from three-way cross method and one check variety (Andungsari 1) as treatments. The tested genotypes were resulted from crossing parents i.e. S 1934, AB 3, RC, YC, S 795, and Catimor that was planted in 1997. The results of the agronomic performance evaluation showed that TWC (Tree Way Cross) 2 ((S 1934/AB 3 x AB 3) x AB 3) and TWC 3 (RC/S 795 x Catimor) had good agronomic characteristics i.e. weight of 100 cherries and cherry weight per tree. While grouping using heatmap clustering method showed that there were three groups of genotypes. One of the groups which consisted of TWC 1 ((S 1934/AB 3 x AB 3) x S 1934), TWC 2 ((S 1934/AB 3 x AB 3) x AB 3), and TWC 5 (S 1934/YC x S 1934) were categorized as moderate yield group.